Supplier value creation configurations in high-cost countries. (23rd October 2019) - Andersen, Poul Houman; Drejer, Ina; Østergaard, Christian R.; Søberg, Peder Veng; Wæhrens, Brian Vejrum
Abstract : Purpose: This paper aims to explore value creation configurations pursued by suppliers in high-cost countries. The proposed value creation configuration approaches are seen as means for supplier firms to strengthen their competitiveness when faced with increasing global sourcing. Design/methodology/approach: Survey data on supplier firms in Denmark are used in a hierarchical cluster analysis. The identified clusters are interpreted as expressions of different value creation configurations pursued by suppliers with regards to relations with their most important customers. Findings: Three types of suppliers are identified: detached suppliers, which seek to create customer net benefits through low costs; technology-focused suppliers, which design value creation around benefits linked to being at the technological forefront; and integrated suppliers, which share characteristics with technology-focused suppliers, but also align closely with a relatively broader range of customer activities. Research limitations/implications: Limitations include the specificity of findings from one small, open economy with an extensive supplier base. Practical implications: For managers in supplier companies, the research suggest value configurations can be used as strategic templates for further specialization and as way to assess and address value creation potential in customer firms. Originality/value: Previous studies tend to overlook suppliers' developments of value-creating activities to maintain customer relationships. The paper takes a supplier perspective to deepen the empirically based understanding of value creation configurations followed by high-cost country suppliers in the context of increasing global competition and production relocation. Theoretical implications as well as lessons formanagers in supplier firms of the identification of the different approaches to value creation configurations are presented.